2022
DOI: 10.1097/j.jcrs.0000000000000978
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in a U.S. registration study of a new EDOF intraocular lens with a nondiffractive design

Abstract: This prospective, randomized study on the nondiffractive intraocular lens (IOL) DFT015 demonstrated superior intermediate and near vision, noninferior distance vision, and comparable visual disturbances to that of a monofocal IOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 16 publications
2
29
2
Order By: Relevance
“…Far vision (binocular UDVA) was 20/20 or better in 77% of patients and at intermediate distance, binocular UIVA was 20/25 or better in 58% of patients. Binocular UDVA and monocular CDVA reported in our study (−0.02 ± 0.07 and −0.04 ± 0.07 logMAR, respectively) are consistent with the results previously reported with the isofocal EDOF lens 17 and slightly better than those obtained with other non-diffractive EDOF IOLs (AcrySof IQ Vivity 13 , 25 , 27 and Tecnis Eyhance 23 , 24 ) and diffractive EDOF IOLs [AT LARA 829MP (Carl Zeiss Meditec) and Tecnis Symfony]. 28 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Far vision (binocular UDVA) was 20/20 or better in 77% of patients and at intermediate distance, binocular UIVA was 20/25 or better in 58% of patients. Binocular UDVA and monocular CDVA reported in our study (−0.02 ± 0.07 and −0.04 ± 0.07 logMAR, respectively) are consistent with the results previously reported with the isofocal EDOF lens 17 and slightly better than those obtained with other non-diffractive EDOF IOLs (AcrySof IQ Vivity 13 , 25 , 27 and Tecnis Eyhance 23 , 24 ) and diffractive EDOF IOLs [AT LARA 829MP (Carl Zeiss Meditec) and Tecnis Symfony]. 28 …”
Section: Discussionsupporting
confidence: 93%
“… 29 AcrySof IQ Vivity with mini-monovision approach provided better binocular UIVA at 66cm and UNVA at 40 cm (0.00 to 0.06 and 0.12 to 0.23) 13 , 15 , 16 than the isofocal EDOF lens in our study. In another AcrySof IQ Vivity study without mini-monovision 27 even the monocular UNVA was as high as 0.15±0.16 logMAR, but interestingly, all patients still needed an addition of at least +1.0 D for near. The better uncorrected intermediate and near visual acuities with AcrySof IQ Vivity IOL compared to other non-diffractive EDOF IOLs, including the isofocal EDOF lens, are likely due to its slightly greater depth of focus, as mentioned before.…”
Section: Discussionmentioning
confidence: 94%
“…This indicates that the Vivity IOL may have a visual disturbance profile that is similar to a monofocal IOL, which has been observed in other studies. 4 , 15 , 16 The reported frequency of glare in this study (55 to 62%) appears to be higher than reports of Vivity and monofocal IOLs in other studies (33 to 53%). 4 , 12 , 16–18 Comparing patient reported outcomes across studies with different endpoints, patient populations, and methodologies is challenging, which may explain these differences.…”
Section: Discussioncontrasting
confidence: 74%
“…The results of our study suggest that the Vivity lens achieves this aim. Two large, multicenter 15 and multicounty 16 studies reported similar visual performance of the Vivity lens compared to a different monofocal IOL (SN60WF AcrySof IQ monofocal; Alcon Vision, LLC).…”
Section: Discussionmentioning
confidence: 96%
“…However, there were some differences in this study when compared with those obtained in the Vivity's U.S. registration trial. 5 In patients bilaterally implanted with the Vivity IOL, the binocular CDVA (À0.01 ± 0.10 [≈20/20] vs À0.028 ± 0.084 [≈20/19]) and DCIVA (À0.02 ± 0.13 [≈20/19] vs 0.054 ± 0.093 [≈20/23]) were similar. 8 However, the DCNVA was 2 lines of vision better in this study (0.03 ± 0.12 [≈20/21]) than that in the U.S. registration trial (0.253 ± 0.118 [≈20/36]).…”
Section: Discussionmentioning
confidence: 99%